Prognostic impact of the Fusobacterium nucleatum status in colorectal cancers. Issue 39 (September 2019) - Chen, Yanglong; Lu, Ying; Ke, Yuting; Li, Yanling
Abstract : Abstract: To investigate the clinicopathological features and prognostic impact of Fusobacterium nucleatum ( F nucleatum ) status in patients with colorectal cancer (CRC) and its relationships with microsatellite instability (MSI) status. Retrospective analysis of consecutive 91 CRC tissues from surgically resected specimens of stage III or high-risk stage II CRC patients who had received curative surgery in Wuhan Union Hospital from January, 2017 to January, 2019 was conducted. F nucleatum DNA was quantitatively measured and classified into 1 of the 2 categories: F nucleatum -high, or F nucleatum -low/negative. The Cox risk ratio model analysis was performed to identify independent risk factors of F nucleatum . F nucleatum -high group was compared with the F nucleatum -low/negative group with respect to clinicopathological features and their relationships with MSI status. Kaplan–Meier method and log-rank test were used for univariate analysis of prognostic factors in patients with CRC. The number of total lymph node acquisition and positive lymph nodes, neurological invasion, vascular tumor thrombus were higher in F nucleatum -high group (27.44 ± 25.213 vs 20.70 ± 10.141; P  = .018; 3.80 ± 7.974 vs 1.74 ± 3.531; P  = .001; 68.0% vs 33.3%; P  = .003; 60.0% vs 25.8%; P  = .002). Moreover, microsatellite mutations were more frequent in patients with F nucleatum -high (84.0% vs 60.6%; P  = .034). A higher abundance of F nucleatum in CRC is associated with a shorter survival time. The F nucleatum status, peripheral nerve invasion, vascular tumor thrombus, lymph node metastasis, and TNM staging were related factors affecting the prognosis of patients with CRC. The Cox risk ratio model analysis showed that the F nucleatum (odds ratio [OR] 2.094, 95% confidence interval [CI] 1.178–8.122, P  = .032) and MSI status (OR 2.243, 95% CI 1.136–5.865, P  = 0.039) were independent prognostic factors. Intratumoral F nucleatum load has a poor prognostic effect of CRC by increasing nerve invasion, vascular tumor thrombus, and microsatellite mutation.